2020
DOI: 10.3354/esr01080
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Hawaii’s humpback whale Megaptera novaeangliae population inferred from male song chorusing off Maui

Abstract: Approximately half of the North Pacific humpback whale Megaptera novaeangliae stock visits the shallow waters of the main Hawaiian Islands seasonally. Within this breeding area, mature males produce an elaborate acoustic display known as song, which becomes the dominant source of ambient underwater sound between December and April. Following reports of unusually low whale numbers that began in 2015/16, we examined song chorusing recorded through long-term passive acoustic monitoring at 6 sites off Maui as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 55 publications
7
34
0
Order By: Relevance
“…Starting in 2014, scientists in Hawaii and Alaska noticed a significant decrease in humpback whale sightings in several areas of known high abundance, coinciding with the Pacific decadal oscillation, Northeast Pacific heatwave, and an El Niño event in 2016 (Gabriele et al, 2017;Cartwright et al, 2019). An acoustic study from Maui showed a decline in daily song levels starting in the 2015/2016 season and persisting through 2018/2019 when levels increased again at some sites (Kügler et al, 2020). Our data show a similar decline in humpback song presence at Kona, beginning in the 2015/2016 season and persisting until the end of the data in 2019, with a concurrent reduction in season length.…”
Section: Long Term Temporal Humpback Trendssupporting
confidence: 64%
“…Starting in 2014, scientists in Hawaii and Alaska noticed a significant decrease in humpback whale sightings in several areas of known high abundance, coinciding with the Pacific decadal oscillation, Northeast Pacific heatwave, and an El Niño event in 2016 (Gabriele et al, 2017;Cartwright et al, 2019). An acoustic study from Maui showed a decline in daily song levels starting in the 2015/2016 season and persisting through 2018/2019 when levels increased again at some sites (Kügler et al, 2020). Our data show a similar decline in humpback song presence at Kona, beginning in the 2015/2016 season and persisting until the end of the data in 2019, with a concurrent reduction in season length.…”
Section: Long Term Temporal Humpback Trendssupporting
confidence: 64%
“…Our analysis revealed only a small correlation between automated humpback whale detections and soundscape metrics, which have been used by other researchers to monitor and quantify humpback whale presence at other locations in the Hawaiian Islands (e.g., Au et al, 2000;Kügler et al, 2020). There were likely other sound sources in our data set contributing to the 125 Hz octave levels, adding to the signals of the whales in this band.…”
Section: The Contribution Of Biological Signalsmentioning
confidence: 60%
“…Here sound from biological sources is predicted to contribute the most to the soundscape. For example, the peaks in SPL at 315 and 630 Hz decidecade bands from February to March at the Hawaiian Islands site likely reflect the nearly continuous vocalizations from humpback whales who arrive during this time to breed (Au et al, 2000;Lammers et al, 2011;Kügler et al, 2020). The American Samoa and Caribbean Sea site soundscapes were likely influenced by fish and invertebrates in addition to humpback whales (Kaplan et al, 2015;Haver et al, 2018Haver et al, , 2019Lillis and Mooney, 2018).…”
Section: Discussionmentioning
confidence: 99%